Corruption as the Main Problem of Russia's Competitiveness - Olga RUDAKOVA; Elena KOLESNICHENKO; Lyudmila KUZNETSOVA; Natalia PYANOVA (Communications of International Proceedings, 2020)
The end of the XXth– beginning of the XXIst century is characterized by the significant increase of competition basically at all world markets. For Russia, full-fledged entry into the global system of the world economy acts, on the one hand, as a vital resource for development, on the other hand, as a threat of displacement to the periphery of the world economy. From this point of view, it is relevant to analyze general trends in ensuring national competitiveness worldwide and for the Russian economy in particular. The current stage of economic development brings to the fore the issue of increasing the competitiveness of the Russian economy. The main weaknesses of Russia's competitiveness are related to administrative procedures and rules. Corruption in Russian society today is one of the main internal risk factors. Nowadays, it has turned from a trivial criminal problem into a key threat to Russia's competitiveness.
Keywords: Competition; Hypercompetition; National Competitiveness; Competitiveness Rating; Problems of Competitiveness; Corruption; Corruption Perception Index; Globalization; World Economy.